The role of plants in Jon Silkin's Holocaust memorial poems. Issue 12 (2nd December 2021) - Phillips, Hannie
ABSTRACT: This essay argues that plants are an integral part of Jon Silkin's poetic memorialisation of the Holocaust. The distinctiveness of Silkin's Holocaust memorial poetics lies in its suggestion that plants can be witnesses to memory of the Holocaust. Silkin's plant witnesses demonstrate human-like capacity for empathy and affect, as the boundary of species between plants and humans is reconstituted. In this essay I analyse three poems from the span of Silkin's career, 'Milkmaids' (1964), 'The People' (1974), and 'Trying to Hide Treblinka' (1992), which each defamiliarise concentration camp sites by depicting them as natural spaces where plants grow. In reading these poems, I consider the ecological form of memorialisation that Silkin creates, exploring what poetry at the interface between ecological poetics and Holocaust memorialisation can look like. I consider the implications this poetics has for an alternative understanding of the spatialisation of Holocaust memory.